2018
DOI: 10.1097/mnm.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose PET/CT and dynamic contrast-enhanced MRI as imaging biomarkers in malignant pleural mesothelioma

Abstract: F-FDG PET/CT and DCE-MRI give prognostic information in malignant pleural mesothelioma. Neither PET/CT nor DCE-MRI is useful for monitoring disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…Analyzing the full-text version of the remaining 31 studies, there were 12 excluded (4 articles including patients with MPM recurrence); 3 articles from the same referring center; 3 articles including MPM patients with both baseline (pre-treatment) and post-treatment PET, but not reporting prognostic analysis of baseline PET data; 1study with a prognostic analysis performed only in a subgroup population; and 1 article including patients with both peritoneal and pleural mesothelioma, with no separate information on MPM subgroup). Finally, 19 studies were included and analyzed in this review [ 29 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing the full-text version of the remaining 31 studies, there were 12 excluded (4 articles including patients with MPM recurrence); 3 articles from the same referring center; 3 articles including MPM patients with both baseline (pre-treatment) and post-treatment PET, but not reporting prognostic analysis of baseline PET data; 1study with a prognostic analysis performed only in a subgroup population; and 1 article including patients with both peritoneal and pleural mesothelioma, with no separate information on MPM subgroup). Finally, 19 studies were included and analyzed in this review [ 29 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Main clinical characteristics of all the included studies are summarized in Table 1 . Regarding the study design, all except two studies [ 34 , 46 ] were retrospective. When considering study population, a heterogeneous sample size was observed, ranging from 23 to 188 patients, with only 5/19 studies enrolling more than 100 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MR has higher sensitivity and specificity in the discrimination of benign and malignant pleural disease; 98-100% and 92-93% respectively (6). In a recent study comparing the results of FDG PET/CT and dynamic contrast enhanced MRI in the evaluation of malignant pleural mesothelioma have showed that prognostic information regarding overall survival might be predicted by SUV max levels while MRI washout curve shape is related with overall survival as well (7). Another prospective study with the patients with diagnosis of unresectable malignant pleural mesothelioma showed that SUV max is correlated with progression free and overall survival and chemoterahy response potential (8).…”
Section: Discussionmentioning
confidence: 99%
“…PET-CT may also be a useful tool for identifying potential biopsy sites. Baseline metabolic activity on PET-CT appears to correlate with survival in mesothelioma [48]. Abrams biopsies are associated with low diagnostic yields and significant complications, and should be avoided where possible.…”
Section: New Directionsmentioning
confidence: 99%